Preparation of Titanium Metal by Deoxygenation Under KCl-NaCl-YCl3 System Using Soluble Anode - Tianzhu Mu; Fuxing Zhu; Yan Zhao; Haoyu Fang; Haohang Ji; Lei Gao (Metals)
Titanium metal is primarily produced via the Kroll process, which is characterized by a semi-continuous production flow and a lengthy process cycle, resulting in high production costs. Researchers have explored alternative methods for titanium production, including molten salt electrolysis, such as the Fray–Farthing–Chen (FFC), Ono Suzuki (OS), and University of Science and Technology Beijing (USTB) processes, aiming to achieve more economical production. Among these, the USTB process, a representative of soluble anode electrolysis, has shown significant promise. However, controlling oxygen concentration in titanium produced by soluble anode electrolysis remains a challenge. This study proposes a novel approach to enhance deoxidation efficiency in soluble anode electrolysis for titanium production by introducing yttrium chloride (YCl3) into the molten salt electrolyte. Thermodynamic analysis and experimental validation demonstrate that the theoretical deoxidation limit for titanium can reach below 100 ppm under Y/YOCl/YCl3 equilibrium. We report the successful synthesis of titanium powder with an oxygen concentration of 6000 ppm from titanium-carbon-oxygen solid solution. Under optimized conditions, the purity of the titanium powder reached 99.42%, demonstrating a new approach for producing high-purity titanium. This method, based on soluble anode electrolysis, offers a potential alternative to the conventional Kroll process. The research elucidates the fabrication process and analytical methods for titanium-carbon-oxygen solid solution, and employs a combination of analytical techniques, including XRD, SEM-EDS, and ONH Analyzer, for characterization of the electrolytic product, encompassing phase analysis, microstructure, and oxygen concentration testing.